Cognition, fear, and falls: psychological predictors of balance impairment in community-dwelling older adults - Batool Abdulelah Alkhamis; Basant Hamdy Elrefaey; Mohammad A. Almohiza; Khalid A. Alahmari; Mastour Saeed Alshahrani; Hani Hassan Alnakhli; Ghada Koura; Debjani Mukherjee; Saleh M. Kardm; Faisal M. Alyazedi; Ravi Shankar Reddy (Frontiers in Psychiatry)
ObjectiveThis study aimed to (1) assess the associations among cognitive function, fear of falling, and balance in community-dwelling older adults; (2) identify key predictors of balance performance; and (3) examine implications for fall prevention strategies.MethodsEighty-four older adults (≥65 years) residing independently in the community were recruited during outpatient visits. Cognitive function was assessed using the Saint Louis University Mental Status (SLUMS), fear of falling was measured with the Falls Efficacy Scale-International (FES-I), and balance performance was evaluated using the Berg Balance Scale (BBS). Physical activity, demographic factors, and fall history were also recorded.ResultsBivariate correlations showed that higher cognitive function was associated with better balance (r = 0.45, p = 0.014), while greater fear of falling was linked to poorer balance (r = -0.52, p = 0.003). A hierarchical regression model revealed that cognitive function (β = 0.32, p = 0.002) and fear of falling (β = -0.44, p < 0.001) were significant predictors of balance performance, even after controlling for age, gender, physical activity, and fall history. Exploratory logistic regression showed that fear of falling (OR = 1.12, p = 0.002) and balance performance (OR = 0.91, p = 0.008) were significant predictors of fall history.ConclusionCognitive function and fear of falling are independent and meaningful predictors of balance performance in older adults. These findings support the integration of cognitive and psychological assessments into exercise-based fall prevention strategies.